THE LEGAL EXPLANATION OF EARLY MARRIAGE AROUND STUDENTS AT SMA PLUS AL HASAN IN KEMIRI VILLAGE PANTI DISTRICT, JEMBER REGENCY - Galuh Puspaningrum; Emi Zulaika; Rama Wisnu Wardana (UNEJ e-Proceeding, 2022)
Marriage is an inner and outer bond between a man and a woman to form a happy and eternal family, which is legalized according to their respective religions and beliefs. The state regulates the minimum age limit for a man and a woman to get married, for men a minimum of 19 (nineteen) years and women at least 16 (sixteen) years. Although this has been regulated in the legislation, it does not prevent the practice of early marriage. Because on the one hand the state also provides opportunities for couples who want to get married early on condition that they must obtain parental dispensation which is then ratified by the local Religious Court. The rise of early marriage among students has an impact on schools, families and the environment. The purpose of this community service is to provide understanding and assistance for students in order to prevent the rise of early marriage among students of SMA Plus Al-Hasan. Keywords : Legal Counseling, Early Marriage, Students, SMA Plus Al Hasan